Pengaruh Green Marketing Concept dan Social Media Marketing terhadap Minat Beli Cookie Cup pada Kafe Monday Coffee Co. Dago Bandung - Herdianto, Avrilla Tri; Nurnida, Ida (eProceedings of Management, 2025)
AbstractResearchers are very concerned about Green Business, especially at this time, that plastic waste has become a bigissue that is quite disturbing to the environment. This study aims to examine the influence of Green Marketing Conceptand Social Media Marketing on Interest in Buying Cookie Cups at Monday Coffee Co. Dago Cafe, Bandung. Theapproach used in this study is quantitative with the type and method of causality descriptive research. Sampling wasconducted using a non-probability sampling method with an accidental sampling sample type with a total of 100respondents. The data analysis techniques used are descriptive analysis and multiple linear regression analysis. Theresults showed that Green Marketing had a significant effect on buying interest with a tcal value of 2,119 in ttable =1,984 with a significance of 0.037. Social Media Marketing has a significant effect on buying interest with a tcountvalue of 3,955 in the table of 1,984 with a significance of 0.000. Simultaneously, the variables Green Marketing andSocial Media Marketing had a significant effect on buying interest with a value of fcal = 35,109 on ftable = 3.09 witha significance of 0.000. The contribution of the influence of Green Marketing and Social Media Marketing variableson Buying Interest is 42%, which shows an R square value (determination coefficient) of 0.042.Keywords-green marketing, social media marketing, <buying= <interest=, cookie cup, café monday coffee Co.